2015
DOI: 10.1108/cg-05-2015-0066
|View full text |Cite
|
Sign up to set email alerts
|

Divergence or convergence: paradoxes in corporate governance?

Abstract: Purpose – This review paper aims to compare the various dimensions in the finance literature pertaining to the Anglo-Saxon Model (Stockholder Model) prevalent in the USA and the UK with the German Model (Stakeholder Model) of corporate governance prevalent in Germany and continental Europe. The present study identifies different strands of research on the various dimensions of these models, along with aspects of governance in emerging economies and the phenomenon of the convergence of these gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 64 publications
1
15
0
1
Order By: Relevance
“…However, the authors suggested that the gap that interferes with the legal system is the lack of parameters to evaluate public enterprises around the world through the ownership structure. Chhillar and Lellapalli (2015) show that traditional governance models, coupled with the incorporation of Principal-Main conflicts, will result in a hybrid model that will instill the best of the two traditional models. However, convergence in the true sense may not be possible due to fundamental differences regarding the cultural, economic, legal and socioeconomic aspects of the company, as the legal system emphasizes heterogeneous regions in the behavior of investments and doubts in the negotiations in the sphere on stock exchanges.…”
Section: Quantitative Results and Discussionmentioning
confidence: 99%
“…However, the authors suggested that the gap that interferes with the legal system is the lack of parameters to evaluate public enterprises around the world through the ownership structure. Chhillar and Lellapalli (2015) show that traditional governance models, coupled with the incorporation of Principal-Main conflicts, will result in a hybrid model that will instill the best of the two traditional models. However, convergence in the true sense may not be possible due to fundamental differences regarding the cultural, economic, legal and socioeconomic aspects of the company, as the legal system emphasizes heterogeneous regions in the behavior of investments and doubts in the negotiations in the sphere on stock exchanges.…”
Section: Quantitative Results and Discussionmentioning
confidence: 99%
“…The challenges are bound to increase further with the growing complexity of global companies working under different domestic and international environments. These circumstances lead to a new operating environment for companies, and the harmonisation or convergence of CG norms has become imperative (Chhillar and Lellapalli, 2015). There is a considerable need for the emergence of CG infrastructure; therefore, the implementation of the global standards embodied by the OECD principles of CG becomes vital to succeed, and the regulator of governance standards requires companies to make a concerted effort to achieve compliance and enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, existem outros tipos de conflitos de interesses, que são pouco observados nas investigações teóricas e empíricas. Um exemplo disso é o conflito de interesses entre principais, ou seja, entre acionistas majoritários e acionistas minoritários, que prevalece em empresas cuja propriedade é concentrada, com baixa proteção ao investidor (Chhillar & Lellapalli, 2015). Outro conflito de interesse pouco explorado nas pesquisas é entre credores e gestão/acionistas, uma vez que os credores fornecem recursos e possuem direitos sobre o fluxo de caixa da empresa, instituindo assim covenants.…”
Section: Oportunidades De Pesquisaunclassified